Rancang Bangun Alat Fiksasi Pemeriksaan Emergency Radiologi pada Ekstremitas Bawah - Chusnul Fadilah Sahudin; Ildsa Maulidya Mar'athus Nasokha; Retno Wati (Lembaga Pengembangan Kinerja Dosen, 2025)
Lower extremity injuries, especially femur and cruris fractures, are quite common in Indonesia. In emergency cases, lateral radiographic examinations with horizontal beam directions often experience distortion and object cutting due to difficulties in placing the cassette. Therefore, a fixation device is needed that can support the position of the cassette and the examination object to produce optimal radiographs. This study used an experimental approach with a design and construction method. Data collection was carried out through functional and performance tests of the fixation device at the Klaten Islamic Hospital, as well as an assessment using a checklist questionnaire to three experienced radiographers. The fixation device was successfully designed in an L shape, made of iron plate with additional foam for patient comfort. The results of the functional test showed a success rate of 90%, met the criteria for feasibility (> 75%), indicating that the fixation device was able to support the cassette and object stably and minimize distortion in emergency radiographic examinations of the lower extremities. The design and construction of this fixation device is effective in improving the quality of emergency radiographic examinations of the femur and cruris. This device is feasible to use with potential improvements in the aspect of ease of mobility for more optimal use in the future.